Peningkatan Ekonomi Masyarakat Melalui Pelatihan Pemanfaatan Handuk Bekas Sebagai Produk Kerajinan Tangan - Amey Makahity; Wenseslaus Rurum; Marsel Marthin Nikijuluw; Indriyanti Kendy; Ronald D. Hukubun (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The community service team provides training on making flower pots by using used goods in the form of towels or cloth. This activity aims to provide new experiences and innovations for young people in Seilale in improving the welfare of the community in an area. By providing creative economic training in making pots from used goods in the form of towels or cloth. This training activity was carried out using the lecture method. This activity is in collaboration with the youth of Seilale village, Nusaniwe sub-district, Ambon city. The result of community service activities is creative economic training in making pots from used goods in the form of towels or cloth. This training was declared successful because the participants were able to carry out and make pots well, and the participants were enthusiastic in participating in the training from beginning to end.